2015
DOI: 10.1515/mammalia-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dental microwear texture analysis and diet in extant Suidae (Mammalia: Cetartiodactyla)

Abstract: International audienceWe investigated the dietary differences among four extant suid genera using 3D dental microwear texture analysis on the enamel surfaces of molar shearing facets. We tested the differences among four taxa for four variables: complexity, anisotropy, and heterogeneity at two scales. This enabled us to distinguish omnivorous taxa (Sus scrofa and Potamochoerus sp.) from herbivorous ones (Phacochoerus africanus and Hylochoerus meinertzhageni) in terms of complexity. Heterogeneity likely disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 39 publications
5
30
0
7
Order By: Relevance
“…meinertzhageni ) in terms of complexity, and heterogeneity distinguished specialized diet of P . africanus from the other taxa (Souron, Merceron, et al, ). In addition, the results of this study demonstrates that the omnivorous suids from the tropics, Potamochoerus and Babyrousa , differ from the generalist S .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…meinertzhageni ) in terms of complexity, and heterogeneity distinguished specialized diet of P . africanus from the other taxa (Souron, Merceron, et al, ). In addition, the results of this study demonstrates that the omnivorous suids from the tropics, Potamochoerus and Babyrousa , differ from the generalist S .…”
Section: Discussionmentioning
confidence: 95%
“…The two species have been found to have different dental microwear texture (Lazagabaster, ). However, Souron et al () did not find similar differences, which can be result from differences in technical parameters or the sampling of different populations. The difference found by Lazagabaster () might occur due to the ecological differences in their habitats, P .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More specifically, an increase in dietary abrasiveness is expected to result in higher texture anisotropy (epLsar) and lower complexity (Asfc). Indeed, previous studies on wild, modern ungulates have shown that grazers have lower complexity and higher anisotropy than mixed feeders and browsers (Merceron et al, 2014;Schulz et al, 2013b;Scott, 2012;Souron et al, 2015;Ungar et al, 2007). 2D microwear analyses of herbivorous and omnivorous muroid rodents point to the same patterns (e.g.…”
Section: Introductionmentioning
confidence: 81%
“…This parameter has been proposed to be an indicator of dietary breadth Souron et al, 2015; but see Schulz et al, 2013a). Two outliers were identified (outside of 1.5 times the interquartile range) in summer in Olszowa Droga.…”
Section: Methodsmentioning
confidence: 99%